1998
DOI: 10.1002/pro.5560071016
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation states of mitochondrial malate dehydrogenase

Abstract: The oligomeric state of fluorescein-labeled mitochondrial malate dehydrogenase (L-malate NAD+ oxidoreductase; mMDH; EC 1.1.1.37), as a function of protein concentration, has been examined using steady-state and dynamic polarization methodologies. A "global" rotational relaxation time of 103 k 7 ns was found for micromolar concentrations of mMDH-fluorescein, which is consistent with the reported size and shape of mMDH. Dilution of the mMDHfluorescein conjugates, prepared using a phosphate buffer protocol, to na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Later studies showed that the dimer dissociates (K D ≈ 200 nM) into monomers at low concentrations of MDH (Shore and Chakrabarti 1976; Bleile et al 1977). However, other groups have reported finding no evidence for dissociation of the monomer (Frieden et al 1978; Jaenicke et al 1979; Sanchez et al 1998). Their results indicate that the dissociation constant for the MDH dimer is less than 3 nM.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Later studies showed that the dimer dissociates (K D ≈ 200 nM) into monomers at low concentrations of MDH (Shore and Chakrabarti 1976; Bleile et al 1977). However, other groups have reported finding no evidence for dissociation of the monomer (Frieden et al 1978; Jaenicke et al 1979; Sanchez et al 1998). Their results indicate that the dissociation constant for the MDH dimer is less than 3 nM.…”
mentioning
confidence: 96%
“…Results from size‐exclusion chromatography (Bleile et al 1977; Wood et al 1978), analytical ultracentrifugation (Hodges et al 1977), and intrinsic fluorescence (Wood et al 1981) indicate that MDH dissociates to monomers at pH 5. However, results of a recent fluorescence polarization study indicate that MDH does not dissociate at pH 5 (Sanchez et al 1998).…”
mentioning
confidence: 99%
“…MDH reactivation was measured at 10-min intervals over a period of for 2 h. MDH activity was measured by the procedure described by Sanchez et al (1998). Identical amounts of E. coli DnaK, DnaJ and GrpE (E. coli chaperones were a kind gift of Dr. H. Pesliakas, Institute of Biotechnology, Vilnius) were employed to induce mitochondrial malate dehydrogenase (MDH) reactivation as a control.…”
Section: Nucleotide Sequence Accession Numbersmentioning
confidence: 99%
“…Haber and Bennett employed FP to study antibody–antigen interactions to determine the rotational relaxation time of antibody–antigen complexes of different sizes. FP has also been used to study the dynamics of monomer/dimer formation . Royer et al have studied the effect of salt concentration on histone subunit interactions using fluorescence polarization …”
Section: Introductionmentioning
confidence: 99%
“…FP has also been used to study the dynamics of monomer/dimer formation. [25][26][27] Royer et al have studied the effect of salt concentration on histone subunit interactions using fluorescence polarization. 28,29 Self-interaction chromatography (SIC) is a technique that can provide information about the self-interactions of a given protein, the second virial coefficient (B 22 ) and the effect of mobile phase modifiers on these interactions.…”
Section: Introductionmentioning
confidence: 99%